Relationship between stress coping Factors with stress level during practical training among trainee teachers: a PLS-SEM approach - Ngui, Geok Kim; Lay, Yoon Fah (2015)
Practicum is a highly stressful situation whereby trainee teachers are subjected to a high quality standard, deals with numerous students’ behaviour, adapt with the school climate and so forth. In this stress coping factors comprising of selfefficacy, subjective well-being and emotional intelligence are associated with practicum stress experienced by 137 trainee teachers in the Sabah Teacher Education Institutions (TEIs). Resiliency Scale for Young Adults (RSYA), Teachers’ Sense of Efficacy Scale, the Emotional Intelligence Traits, Satisfaction with Life Scale (SWLS) and Rating Pre-Service Teacher Events for Stress Scale were adapted and used in this study. Collected data were analysed using the PLS-SEM approach. The result showed self-efficacy, emotional intelligence, subjective well-being and stress are moderate but resiliency has moderately low level. Self-efficacy and subjective well-being are significant predictors of resilience and stress, however, emotional intelligence is not. It is hoped that this study will provide more understanding about stress and stress coping abilities so that appropriate orientation, content, and practice during practicum can be planned and implemented in an effort to prepare high quality educators.